Combination Treatment of Icariin and L-DOPA Against 6-OHDA-Lesioned Dopamine Neurotoxicity - Lu, Di-Sheng; Chen, Ce; Zheng, Ya-Xin; Li, Dai-Di; Wang, Guo-Qing; Liu, Jie; Shi, Jingshan; Zhang, Feng (Frontiers in Molecular Neuroscience, 2018)
Until now, the dopamine (DA) precursor, L-3,4-dihydroxyphenylalanine (L-DOPA), remains the gold standard effective drug therapy for Parkinson’s disease (PD) patients. Nevertheless, long-term chronic L-DOPA administration leads to the drug efficacy loss and severe adverse effects, such as L-DOPA-induced dyskinesia (LID). Icariin (ICA), a flavonoid that is extracted from Epimedium, has been proved to evoke neuroprotection against DA neuronal loss in PD animal models. Here, the present study detected the effects of ICA combined with L-DOPA on 6-hydroxydopamine (6-OHDA)-elicited DA neurotoxicity and L-DOPA-induced motor dysfunction as well. PC12 cells were applied to investigate the combination treatment of ICA and L-DOPA against 6-OHDA-lesioned neurotoxicity. In addition, rat substantia nigral stereotaxic injection of 6-OHDA-induced DA neuronal injury was performed to explore the neuroprotective effects mediated by ICA combined with L-DOPA. The pathological movement triggered by L-DOPA was determined by the abnormal involuntary movements (AIM) scores analysis. In PC12 cells, ICA combined with L-DOPA produced better neuroprotection from 6-OHDA-induced neurotoxicity than ICA or L-DOPA alone treatment. In parkinsonian 6-OHDA lesioned rats, ICA conferred DA neuroprotection as monotherapy and an enhancement benefit of L-DOPA treatment after daily administration of L-DOPA and ICA for 21 days. Moreover, ICA ameliorated the development of LID as evidenced by the lowered AIM scores without affecting L-DOPA-mediated efficacy. Furtherly, ICA attenuated neuroinflammation in 6-OHDA-induced DA neuronal loss and the development of LID in vivo. In conclusion, these findings suggest ICA might be a potential promising adjuvant to enhance L-DOPA efficacy and attenuate L-DOPA-produced adverse effects in PD.